Penilaian Mutu Secara Organoleptik Ikan Cakalang (Katsuwonus pelamis) di Pelabuhan Perikanan Pantai Pondokdadap Kabupaten Malang - Yus Isnainita Wahyu; Puji Sugeng Ariadi; Jalal Sayuti (Samakia : Jurnal Ilmu Perikanan, 2019)
The study was conducted in December 2018 at the Coastal Fisheries Port, Pondokdadap, Malang, East Java. The aim was to determine the level of freshness of fish and the difference in freshness of skipjack fish in three different locations such as fish auction sites, supplier / collector warehouses and directly from the fisherman around the Coastal Fisheries Port. The freshness of the fish was determined using organoleptic method. Organoleptic test is a method using the human senses as the main tool in assessing the quality of live fish and fishery products that are still in a fresh condition. After the fish dies there is a change in the fish which leads to rapid decay. The results showed that there were differences of the freshness of fish in three different locations, but it was still in good category of fresh fish.